Perlawanan Masyarakat Dusun Air Abik Dalam Menentang Perluasan Lahan Perkebunan Kelapa Sawit Dilihat Dari Teori Contentious Politics - M. Adha Al Kodri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2016)
In the middle of district head’s euphoria to float and move forward province of Bangka Belitung’s island by brought in the palm oil investors conduce the new conflict of society, i.e agrarian conflicts. The presence of palm oil investors in the middle that in the beginning has been designed to give a profit for society, especially the societies around the oil palm plantation, but precisely harm the soci- ety a lot. For local society, indigenous forest is symbol of nature conservation and the place of animal Seizure and claims over land often happens between the palm oil investors with local society. One of them is the conflict between Air Abik society with PT. Gunung Pelawan Lestari. The main factor of this conflict is there a logging, indigenous forest clearance, destruction of 11 ancestral graves belong to society conducted by PT. Gunung Pelawan Lestari in their efforts to oil palm expansions. This thing then triggered public protest action. survival. Whereas, ancestral grave is symbol of local wisdom and cultural heritage that must be preserved and maintained. Besides, if we see the conflict between both sides, it can be analyzed with contentious politics theory. The use of contentious politics theory because this conflict involves the collective interaction between the claimant, i.e PT. Gunung Pelawan Lestari and claim object, i.e customary land and the land where the 11 ancestral graves stand. In contentious politics theory, there is also depletion of resources. This depletion of resources in the end will influencing people to get involved in the political tensions, like the high level of public complaints, legacy of previous protest, political opportunity structure, and the mechanism relation to help society resistance.